Manajemen Mutu Penyelenggaraan Ruas Jalan Ciawi-Puncak Menggunakan Analisa Iri dan SDI (Studi Kasus Penentuan Program Penanganan Ruas Jalan Ciawi-Puncak) - Suparman; Hary Agus Rahardjo; Dwi Dinariana (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2024)
Ciawi-Puncak’s Road Line of West Java of Province constitute one of National Road of where location in Puncak-Bogor Area, where has flexible pavement construction and having wide road line about 7-10 meter and to has standard wide road value line of National Road Status of Ministry of Public Work and People Housing. Program of Road Maintenance of Ministry of Public Work and People Housing to having a software system that used for planning national road maintenance viz IIRMS Guidline (Indonesian Integrated Road Management System). One of IIRMS Applacation is Road Condition Survey (RCS). The Survey of Ciawi-Puncak’s Road Line of West Java of Province with using RCS application for obtain International Roughness Index (IRI) and Surface Distress Index (SDI) base on calculation of BinaMarga method for knowing degree and detriment type of road condition in maintenance program planning both handling or implementation of road routine maintenance, periodic maintenance/road rehabilitation and road structure enhancement. Survey of road condition on this research is done Ciawi-Puncak’s Road Line of West Java of Province with long road around ± 22.500 meter.